Acute caffeine ingestion's increase of voluntarily chosen resistance-training load after limited sleep - Cook, C.; Beaven, C. M.; Kilduff, L. P.; Drawer, S. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
This study aimed to determine whether caffeine ingestion would increase the workload voluntarily chosen by athletes in a limited-sleep state. Methods: In a double-blind, crossover study, 16 professional rugby players ingested either a placebo or 4 mg/kg caffeine 1 hr before exercise. Athletes classified themselves into nondeprived (8 hr+) or sleep-deprived states (6 hr or less). Exercise comprised 4 sets of bench press, squats, and bent rows at 85% 1-repetition maximum. Athletes were asked to perform as many repetitions on each set as possible without failure. Saliva was collected before administration of placebo or caffeine and again before and immediately after exercise and assayed for testosterone and cortisol. Results: Sleep deprivation produced a very large decrease in total load (p = 1.98 × 10-7). Caffeine ingestion in the nondeprived state resulted in a moderate increase in total load, with a larger effect in the sleep-deprived state, resulting in total load similar to those observed in the nondeprived placebo condition. Eight of the 16 athletes were identified as caffeine responders. Baseline testosterone was higher (p < .05) and cortisol trended lower in non-sleep-deprived athletes. Changes in hormones from predose to preexercise correlated to individual workload responses to caffeine. Testosterone response to exercise increased with caffeine compared with placebo, as did cortisol response. Conclusions: Caffeine increased voluntary workload in professional athletes, even more so under conditions of self-reported limited sleep. Caffeine may prove worthwhile when athletes are tired, especially in those identified as responders.